KAPITALISME PEDAGANG MUSLIM TEMBORO: ANTARA KETAATAN BERAGAMA DAN KEUNTUNGAN EKONOMI - Muhamad Misbahudin; Diyan Putri Ayu (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2023)
This paper explores and explains how Temboro Muslim traders build their relationship with the coexistence of Islamic commodification with the business world. This anthropological sociology research uses ethnographic methods focusing on traders working in the Temboro Islamic Boarding School, Magetan, East Java market. The focus is on the activities of Temboro Muslim traders and forms of trade as well as the affinity between religion as a source of teachings and the economy. This paper argues that in Temboro, as an area influenced by the existence of Islamic boarding schools, the Muslim community flocked to come and settle around the Islamic boarding school to trade. They then become a group of devout Muslims who try very hard to maintain and preserve the "real" Islamic identity by returning to the Koran and Sunnah by accumulating in the ideological power presented by the pesantren. This condition has significantly changed the expression of the economy built by traders about the cultural and religious landscape of the santri.